Dakwah walisongo dan integrasi nilai psikologis dalam pembentukan peradaban islam di jawa - Ramadhani, Safira Dhia (Maliki Interdisciplinary Journal, 2026)
This study examines the role of Walisongo's preaching in the process of spreading Islam in Java by highlighting the integration of Islamic values, local culture, and psychological approaches in shaping the character of society. Through a historical approach and literature review, this study discusses the Walisongo's accommodative, humanistic, and arts-based da'wah strategies, such as wayang, tembang, and local traditions as a means of internalizing Islamic values. The results of the study show that the success of the Walisongo's da'wah lies in their ability to combine Islamic teachings with local wisdom without confrontation, thereby giving birth to an inclusive, moderate, and tolerant Islamic identity. Sufi values such as tazkiyatun nafs have been proven to contribute to mental health, inner balance, and social harmony in Javanese society. These findings confirm the relevance of the Walisongo's legacy in representing Islam as a dialogical and transformative civilization of the soul, as well as providing an ethical and conceptual foundation for the development of a holistic, contextual, and humanity-oriented Islamic psychology.